Stimulation of risogenesis of red and black raspberry in vitro with use of coherent radiation - N. V. Solovykh; A. V. Budagovsky (Аграрная наука Евро-Северо-Востока, 2018)
The effect of supplementary red LED and laser lightning on the rhizogenesis in vitro of plants of the genus Rubus at different levels of the basic polychromatic illumination was studied. The relevance of this work is due to the need to improve the biotechnological methods of accelerated plant propagation at all stages of cloning, including root formation stage. One of the ways to solve this problem is to use coherent radiation to stimulate physiological and morphogenetic processes in plants and to create energy-saving cultivation technologies on the basis of the methods developed. Microcuttings of berry crops cultivated with 1000 and 2000 Lux illumination were subjected to daily supplementary lightning for 20 minutes with LEDs (λ = 638 nm, power density 5 W/m2) or helium-neon laser (λ = 632.8 nm, power density 3 W/m2). In conditions of low illumination (1000 Lux), the intensity of rhizogenesis in red raspberry and black raspberry decreased in comparison with the illumination of 2000 Lux. LED-based and laser additional irradiation increased the intensity of the rhizogenesis of berry crops in vitro. With a low basic illumination (1000 Lux) the maximum stimulating effect of an additional red quasi-monochromatic illumination was observed. In red and black raspberry, laser and LED backlighting with insufficient basic illumination made it possible to obtain the number of roots and their total length per one explant not differing statistically from those at full illumination, but without backlighting.